A pilot study on use of live attenuated rotavirus vaccine (Rotarix™) as an infection challenge model. Issue 46 (27th October 2020) - Chilengi, Roma; Simuyandi, Michelo; Chibuye, Mwelwa; Chirwa, Masuzyo; Sukwa, Nsofwa; Laban, Natasha; Chisenga, Caroline; Silwamba, Suwilanji; Grassly, Nicholas; Bosomprah, Samuel
Abstract: Background: Rotavirus remains the commonest cause of dehydrating diarrhoea, particularly in developing countries. Human infection challenge studies in children in these countries offers an opportunity to rapidly evaluate new vaccine candidates that may have improved efficacy. We evaluated use of Rotarix™ as a live-attenuated challenge agent. Methods: We undertook an open label, exploratory study in infants receiving two standard doses of Rotarix™ at 6 and 10 weeks of age in a cohort of 22 Zambian infants. The first vaccine dose was considered as primary vaccination, and the second at day 28 as a live-attenuated virus challenge. Saliva, stool and serum samples were collected on days 0, 3, 5, 7, 14, and 28 following each dose. The primary outcome was stool shedding of rotavirus, determined by NSP2 qPCR. We calculated mean shedding index as average of natural logarithm of viral copies per gram of stool. Findings: After the first dose, viral shedding was high at day 3, peaked by day 5. After the second dose, viral shedding at day 3 was low and reduced gradually in most infants until day 14. Mean shedding index was significantly lower post dose 2 across all infants and timepoints (5.0 virus copies/g of stool [95%CI: 0.3–9.7] vs 10.4 virus copies/g of stool [95%CI: 6.2–14.6]; p-value < 0.0001; rho = 0.20, SD = 4.97. Seroconversion at day 28 was associated with a mean reduction of −1.03 (95%CI = -8.07, 6.01) in viral shedding after challenge dose but this was not statistically significant (p = 0.774). A borderline positive correlation between fold-change in IgA titre at day 28 from day 0 in saliva and serum was observed; Spearman's correlation coefficient, r = 0.69; p = 0.086. Interpretation: Shedding after the 'challenge' dose was reduced compared with the first dose, consistent with the induction of mucosal immunity by the first dose. This supports the use of Rotarix vaccine as a live-attenuated infection challenge. Funding: Medical Research Council (UK) through the HIC-Vac Network